Alcohol Craving in Heavy and Occasional Alcohol Drinkers After Cue Exposure in a Virtual Environment: The Role of the Sense of Presence - Simon, Jessica; Etienne, Anne-Marie; Bouchard, Stéphane; Quertemont, Etienne (Frontiers in Human Neuroscience, 2020)
The development of new technologies, and more specifically the opportunity to immerse participants in virtual controlled environments, provides a new ecological framework for researchers to study complex behaviors. The aim of this experiment was to compare post-immersion craving in occasional and heavy alcohol drinkers. Twenty-two occasional drinkers and eighteen heavy drinkers were recruited and immersed in a virtual bar, including alcoholic beverages. After the exposure, heavy drinkers reported a significantly higher craving than occasional drinkers. Post-immersion alcohol craving was significantly related to the levels of perceived ecological validity of the virtual environment. Finally, a moderation analysis suggested that the levels of craving more strongly increased with perceived ecological validity in heavy drinkers than in occasional drinkers. Therefore, the perceived ecological validity was an important experimental parameter to study craving in a virtual environment. These results further suggested that virtual reality might be a useful tool for both the scientific study of alcohol addiction and the treatment of alcohol dependence and relapse.